O procedimento probatório nos novos modelos processuais - Maia, Gretha Leite (2001)
This work is research object of the acertamento fact issue as an antecedent of by courts through an evidentiary procedure. The theme of the evidence, throughout this research , proved to be multidisciplinary : it involves the necessary analysis of philosophical , psychological, legal , sociological and numerous other sciences , each with its different scientific methods and their particular principles , which made research rather exciting , but it also revealed difficulties in operating order.